188k views
5 votes
How else could you prove if x^3-a^3=(x-a)(x^2+ax+a^2)

1 Answer

5 votes

x^3 - a^3

The above expression represent differnt of 2 cubes

This can be re- written as

(x - a)^3

(x - a) ( x ^2 + ax + a^2)

expand the bracket

x * x^2 + ax*x + x *a^2 - a * x^2 - a * ax - a * a^2

= x^3 + ax^2 + a^2x - ax^2 - a^2x - a^3

collecting the like terms

= x^3 + ax^2 - ax^2 + a^2x -a^2x - a^3

ax^2 - ax^2 = 0

a^2x - a^2x = 0

Therefore

= x^3 + 0 + 0 - a^3

= x^3 - a^3

User Alec Mather
by
4.4k points